Citizen Charter dalam perspektif kebijakan dalam upaya optimalisasi pelayanan perijinan - Arif Budiono; Adji Samudra Trisnatyan; Linda Gusnia (ARISTO, 2017)
Licensing is happening in Indonesia today many responded so negatively. Person who has been processing and licensing world with a policy set in such a manner compatible with the interests of the individual itself.It is inevitable that all of it is due to a culture that is built up culture is that the position of the apparatus is something special and very hierarchical so residents who require bureaucracy. This kind of culture really bad influence so that the paradigm is served rather than serve really contagious. Licensing bureaucracy becomes sluggish bureaucracy, procedural, unresponsive.Roles and permissions bureaucratic culture in the licensing policy may change with the adoption of citizen charters are oriented to the service of citizens. The entire procedure, completeness, groove arrangement, duration and cost of everything listed and published open so known to all citizens.With this openness became clear all parameters and at the same licensing policies oriented to citizens. Innovation bureaucrats to implement licensing in the past is very difficult to do because the system is bureaucratic, procedural and stiff but with citizen charter then stimulated to innovate bureaucracy that facilitates licensing policy.Every innovation and job details become facilitate citizens with side effects is the performance improvement will have positive implications for both the welfare apparatus or in a career, and vice versa will be negative berimpilikasi form of punishment.